THE COLORECTAL CANCER: EPIDEMIOLOGY AND PHENOTYPE OF PATIENTS OF THE REPUBLIC OF KHAKASSIA - Olga Vladimirovna Shtygasheva; Elizaveta Sergeevna Ageeva; Natalya Sergeevna Balobina; Diliya Ismagilovna Manasheva (В мире научных открытий, 2018)
Background. The risk colorectal cancer (CRC) increases with the duration of the course inflammatory bowel disease (IBD), the risk polyp malignancy rises with the size of polyp. The examining and monitoring of hyperplastic and adenomatous polyps plays important role in predictive and early diagnosis of CRC. The aim is research the epidemiological features CRC of Khakassia and frequency of stratify factors of disease risk due to data of vital anamnesis is to form a cohort of patients which must be examine at first.